2022
DOI: 10.3390/foods11233818
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Release of Thymol by Cyclodextrin Metal-Organic Frameworks for Preservation of Cherry Tomatoes

Abstract: Thymol is a phenol monoterpene with potential antifungal, antioxidant and antibacterial activities. Due to the low water solubility and high volatility of thymol, encapsulation serves as an effective tool during application. In the present study, cyclodextrin (CD)-based metal-organic-frameworks (MOFs) were synthesized using α-CD, β-CD, and γ-CD as organic building blocks, and further complexed with thymol to produce three CD-MOF-THY inclusion complexes (ICs). The encapsulation content, release kinetics and fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Li et al . (2022) reported that thymol was released from cyclodextrin‐MOFs for 35 days. The sustained release of thymol allowed its exposure to the fungal cells for a longer period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al . (2022) reported that thymol was released from cyclodextrin‐MOFs for 35 days. The sustained release of thymol allowed its exposure to the fungal cells for a longer period.…”
Section: Resultsmentioning
confidence: 99%
“…The volatile thymol was released continuously even beyond the period when the fungus had already reached its maximum growth after a week of incubation. Li et al (2022) reported that thymol was released from cyclodextrin-MOFs for 35 days. The sustained release of thymol allowed its exposure to the fungal cells for a longer period.…”
Section: Growth Inhibition At 25 °Cmentioning
confidence: 99%
“…didyma) leaves and flowers (MEO) has been confirmed to be a broad-spectrum antiseptic with potential as a food preservative. We previously identified thymol as the principal component of MEO, postulating that it is the compound responsible for MEO’s antimicrobial effects . Studies also demonstrated that thymol, a nontoxic natural product, exhibits remarkable antifungal properties and potential as a food preservative, resulting from the phenolic hydroxyl group pharmacophore constituted in its chemical structure. The research foundation of our collaboration with a company in developing Hippophae rhamnoides L. (H. rhamnoides) resources, along with other studies, indicated the potential of H.…”
Section: Introductionmentioning
confidence: 99%
“…Exploited materials do not act only as protective shells, but they allow a great interaction with target cells and a gradual release in them [ 17 ]. Different systems and materials have been applicated for thymol, including silica colloids, chitosan particles, and cyclodextrins [ 18 , 19 , 20 ]. Hence, nanogel, nanoparticles, and nanoemulsions were studied for optimizing the usage of thymol as a biocide [ 19 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different systems and materials have been applicated for thymol, including silica colloids, chitosan particles, and cyclodextrins [ 18 , 19 , 20 ]. Hence, nanogel, nanoparticles, and nanoemulsions were studied for optimizing the usage of thymol as a biocide [ 19 , 21 , 22 , 23 ]. This is the first report about the investigation of thymol against the quarantine pathogen Xylella fastidiosa .…”
Section: Introductionmentioning
confidence: 99%